2009
DOI: 10.1021/la901389v
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Nanospheres and Vesicles Based on Pectin as Drug Carriers

Abstract: A novel strategy was developed to prepare nanospheres and vesicles as drug carriers. The drug-loaded pectin nanospheres and vesicles were fabricated in aqueous media containing Ca2+ and CO3(2-) ions under very mild conditions, which did not involve any surfactant. Through adjusting the preparation conditions, nanosized drug delivery systems with diverse morphologies, that is, nanospheres and vesicles, could be obtained. This technique could offer good control over the morphology and the size of nanospheres and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 23 publications
1
39
0
1
Order By: Relevance
“…From the dissolution profiles in Fig. 10, it was noted that ionic crosslinking PEC with Ca 2+ reduced the amount of drug released in 24 hours and this may have been a result of the formation of an egg-box network structure when the Ca 2+ electrostatically interacted with the carboxylic moieties of the macromolecular PEC (Yu et al, 2009). This egg-box structure condenses the PEC chains encapsulating AZT leading to reduced dissolution.…”
Section: In Vitro Drug Release From Peg-encl-pec:muc Smmsmentioning
confidence: 99%
“…From the dissolution profiles in Fig. 10, it was noted that ionic crosslinking PEC with Ca 2+ reduced the amount of drug released in 24 hours and this may have been a result of the formation of an egg-box network structure when the Ca 2+ electrostatically interacted with the carboxylic moieties of the macromolecular PEC (Yu et al, 2009). This egg-box structure condenses the PEC chains encapsulating AZT leading to reduced dissolution.…”
Section: In Vitro Drug Release From Peg-encl-pec:muc Smmsmentioning
confidence: 99%
“…Th e unbound carboxylic acid groups will form a hydrophilic shell and allow conjugation of the drug molecule in the drug loading step. According to Yu et al, spherical shape of nanoparticles were achieved when NaHCO 3 were added during nanoparticle preparation (Yu et al, 2009). Th erefore, NaHCO 3 solution was included into the mixture to provide carbonic anions (CO 3 − ) interacting with magnesium ion by electrostatic interaction and stabilize the spherical shape of nanoparticles (Yu et al, 2009).…”
Section: Pectin Nanoparticle Preparation and Characterizationmentioning
confidence: 99%
“…According to Yu et al, spherical shape of nanoparticles were achieved when NaHCO 3 were added during nanoparticle preparation (Yu et al, 2009). Th erefore, NaHCO 3 solution was included into the mixture to provide carbonic anions (CO 3 − ) interacting with magnesium ion by electrostatic interaction and stabilize the spherical shape of nanoparticles (Yu et al, 2009). In addition, it has been reported that the size of nanoparticles formed via the electrostatic interaction were reduced when magnesium cation was used compared to other positively charge cations such as calcium cation (Opanasopit et al, 2008).…”
Section: Pectin Nanoparticle Preparation and Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The separation of cells from the host tissue enhances the efficacy and viability of transplanted cells. 18 Likewise, they are used to encapsulate microorganisms ͑e.g., yeast 19 for the fermentation processes͒ or active substances like drugs, 14,20 enzymes, 11 or even blood proteins. 21 As opposed to traditional, physicochemical methods of encapsulation, also here microfluidics comes in with a unique advantage of the possibility to encapsulate virtually any material in any matrix via the hydrodynamic control of the process of formation of particles.…”
Section: Introductionmentioning
confidence: 99%